Financial Ratio Analysis to Predict Financial Distress on Property and Real Estate Company listed in Indonesia Stock Exchange - Imas Nurani Islami; William Rio (JAAF (Journal of Applied Accounting and Finance), 2018)
This study aims to prove the ability of financial ratios in measuring financial distress. As is known that the start of the number of new companies that compete in order to achieve corporate goals, even more national companies that want to compete with foreign companies. On this basis, researchers attempt to prove the probability of occurring financial distress by using several financial ratios, especially large companies such as property and real estate firms. The financial ratios used in this study are current ratio, debt ratio, return on equity ratio, and capitalization ratio. With the type of research that is quantitative, the population that has been used in this study are property and real estate companies listed on the Indonesia Stock Exchange period 2012-2016. -. The sample obtained is a company that continuously publish its financial report within five years. According to the results of research that has been done, the ratio is able to measure the possibility of financial distress in property companies and real estate is the current ratio, debt ratio, and return on equity ratio. While the ratio is not able to measure the likelihood of occurrence of financial distress is capitalization ratio.